Nanoparticulate magnetite thin films as electrode materials for the fabrication of electrochemical capacitors - Pang, S.C.; Khoh, Wai Hwa; Chin, S.F. (Springer, 2010)
Magnetite nanoparticles in stable colloidal suspension were prepared by the co-precipitation method. Nanoparticulate magnetite thin films on supporting stainless steel plates were prepared by drop-coating followed by heat treatment under controlled conditions. The effects of calcination temperature and atmosphere on the microstructure and electrochemical properties of nanoparticulate magnetite thin films were investigated. Nanoparticulate magnetite thin films prepared under optimized conditions exhibited a specific capacitance value of 82 F/g in mild aqueous 1.0 M Na2SO4 solution. Due to their high charge capacity, good cycling reversibility, and stability in a mild aqueous electrolyte, nanoparticulate magnetite thin films appear to be promising electrode materials for the fabrication of electrochemical capacitors.